2017
DOI: 10.1002/elps.201700372
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone‐based colorimetric chiral recognition of ibuprofen using aptamers‐capped gold nanoparticles

Abstract: Sensitive and fast detection of ibuprofen enantiomers is very critical for required routine monitoring and risk assessment of trace pollutants in water samples. Here a simple, rapid and highly sensitive android smartphone application for chiral recognition was developed. Aptamer-capped gold nanoparticles (AuNPs) was demonstrated as an efficient detection platform for (S)-(+)-ibuprofen (S-Ibu) and (R)-(-)-ibuprofen (R-Ibu). Detachment of an enantioselective aptamer from the AuNPs surface and binding with an ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…To understand the risks associated with secondhand exposure to these compounds, it is necessary to develop highly sensitive and specific biosensors for their detection in environmental sources. In particular, commonly prescribed medications like the chemotherapeutic agent doxorubicin (Bahner et al, 2018), common pain reliever ibuprofen (Ping et al, 2018), hormonal birth controls and hormone replacement therapies, and antibiotics have been the focus of recent biosensor efforts. In fact, a simple smartphone based portable colorimetric biosensor for the detection of ibuprofen was described which could detect the molecule in tap water and river water at spiked concentrations in the low ng/mL range (Ping et al, 2018).…”
Section: Pharmaceuticalsmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the risks associated with secondhand exposure to these compounds, it is necessary to develop highly sensitive and specific biosensors for their detection in environmental sources. In particular, commonly prescribed medications like the chemotherapeutic agent doxorubicin (Bahner et al, 2018), common pain reliever ibuprofen (Ping et al, 2018), hormonal birth controls and hormone replacement therapies, and antibiotics have been the focus of recent biosensor efforts. In fact, a simple smartphone based portable colorimetric biosensor for the detection of ibuprofen was described which could detect the molecule in tap water and river water at spiked concentrations in the low ng/mL range (Ping et al, 2018).…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…In particular, commonly prescribed medications like the chemotherapeutic agent doxorubicin (Bahner et al, 2018), common pain reliever ibuprofen (Ping et al, 2018), hormonal birth controls and hormone replacement therapies, and antibiotics have been the focus of recent biosensor efforts. In fact, a simple smartphone based portable colorimetric biosensor for the detection of ibuprofen was described which could detect the molecule in tap water and river water at spiked concentrations in the low ng/mL range (Ping et al, 2018). In this assay, the colorimetric signal generation depended on the interaction of the aptamers (both selected by Kim et al, 2010 and were reported to have micromolar K d s), AuNPs, and the target molecule (S-or R-ibuprofen) in a mechanism that was similar to the assay described in Figure 6.…”
Section: Pharmaceuticalsmentioning
confidence: 99%
“…A smartphone‐based colorimetric method using aptamer‐capped Au nanoparticles was applied for quantitation of ibuprofen enantiomers, with LODs of 1.24 and 3.91 pg mL –1 for S‐ and R‐ibuprofen, respectively . Ibuprofen is a common drug to treat fever and pain, and its S‐form is more pharmacologically active.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…The aptamers are placed on the surface of AuNPs to prevent them from aggregation via electrostatic repulsion of aptamers. In presence of their target, the aptamers detach out from the AuNPs surface to bind their own targets inducing the nanoparticle aggregation thereby changing its visible color [ 49 , 50 ]. In addition, other materials are also used in colorimetric aptasensor including peroxidase-like activity of graphene/nickel@palladium hybrids [ 51 ] and hemin-functionalized reduced graphene oxide (hemin-rGO) composites [ 52 ].…”
Section: Aptasensors and Their Applications For Detecting Low Molementioning
confidence: 99%